Part I: understanding pain in pigs—basic knowledge about pain assessment, measures and therapy - Julia Kschonek; Lara Twele; Kathrin Deters; Moana Miller; Jennifer Reinmold; Ilka Emmerich; Isabel Hennig-Pauka; Nicole Kemper; Lothar Kreienbrock; Michael Wendt; Sabine Kästner; Elisabeth grosse Beilage (Porcine Health Management)
Abstract Background Pigs can suffer from pain due to spontaneously occurring diseases, wounds, injuries, trauma, and physiological conditions such as the farrowing process; however, this pain is often neglected. To increase knowledge and awareness about this phenomenon, the current article presents a scoping review of basic and new approaches for identifying, evaluating, and treating pain in pigs. Methods A scoping review was conducted with results from a search of the electronic database VetSearch and CABI. With regard to eligibility criteria, 49 out of 725 publications between 2015 and the end of March 2023 were included. The findings are narratively synthesized and reported orienting on the PRISMA ScR guideline. Results The results of this review showed that practitioners need to consider pain not only as a sign of a disease but also as a critical aspect of welfare. If both the symptoms of pain and the underlying reasons remain unassessed, the longevity and prosperity of pigs may be at risk. In this respect, veterinarians are obliged to know about intricacies of pain and pain mechanisms and to provide adequate treatment for their patients. Conclusion It is pivotal to increase knowledge about pain mechanisms, the reasons for heterogeneity in behavioural signs of pain, and methods for evaluating whether a pig is experiencing pain. This article will help practitioners update their knowledge of this topic and discuss the implications for everyday practice.